ENT 530 Social Media Portfolio: Bold Beaute / Azhana Haziqah Azmi - Azmi, Azhana Haziqah (2021)
Bold Beaute is a business that sell makeup product or specifically selling lipstick. The aim of Bold Beaute is to make every girl to be more confident and beautiful at the time by produced various types of lipstick shades that suitable with all type of color skin and at the same time maintaining the quality. This reports provides the promotional of the product on the social media to introducing the product and the brands of Bold Beaute starting with creating the Facebook page, the URL of the page, the teaser, soft sell and lastly hard sell. Firstly, I will explain all the information about the background of the product in the introduction such as the mission & vision, description of the product and also the product price list. As a final point, I will conclude progress of the product by include all promotional posting on the social media where I use the Facebook platform for the posting.